Is culture a excluding factor for health care in Bolivia? Evidence of maternal health care utilization - Christian A. Valencia (Institute for Advanced Development Studies (INESAD), 2013)
This document states the hypothesis that there are some cultural factors that are negatively related to health care utilization. Evidence of maternal health care is used to assess the hypothesis. Two different dependent variables are used, antenatal care and delivery assistance with a health professional. The set of covariates include predisposing factors (individual, household and cultural factors), characteristics of morbidity and characteristics of health system. Using the 2008 Demographic Health Survey (DHS) this document presents estimations of a logit model and average marginal effects. Results show that cultural factors are negatively related to health care utilization, through the estimation of its variables, self identification as native, first language and state. Yet, some individual characteristics as education and mainly wealth present higher significances. Therefore, short run policies should focus on improving wealth for selected groups of excluded women rather than other policies as improving education.
Keywords: I15; I18; C25; 330; maternal health; antenatal care; delivery assistance; models for binary data; Bolivia